Pneumocystis carinii pneumonia and reticuloses - Humphries, Keith R. (1968)
Three cases of Pneumocystis carinii pneumonia occurring in the course of diseases of the lymphoreticular system are described. One case was diagnosed in life and unsuccessfully treated with pentamidine isethionate. Incidence of the pneumonia is associated with a depressed immune response and may be more frequent than is usually realized in patients with reticuloses who are receiving corticosteroid and cytotoxic drugs.